Batik Semarang on Cultural Ecology Perspective: Characteristic of Visual Expression - Intan, Noor Tiara Habib Aisyah; Sugiarto, Eko; Wibawanto, Wandah (Universitas Negeri Semarang, 2023)
Batik is a traditional textile work of art which was designated by UNESCO on 2 October 2009 as an intangible cultural heritage (representative List of the Intangible Cultural Heritage of Humanity). This research aims to analyze the characteristics of Semarang batik based on cultural ecology, especially the Semarang icon category, the case study of this research is at IKM Batik Semarang 16. This research is qualitative research, in this research uses several theoretical approaches, namely a visual analysis approach with color theory and design principles for analyzing the visual elements in batik motifs. Apart from using a visual analysis approach with color theory and design principles, a cultural ecology approach will also be discussed to discuss the cultural ecological aspects found in batik motifs, especially in the Lawang Sewu Ngawang, Mberok Bridge, Tugu Muda Kekiteran Sulur, and Blekok Srondol motifs. The cultural ecology approach is used to understand the complex relationship between humans, culture and the environment in the context of batik production and use in the city of Semarang, Central Java. The results of this research show that the characteristics of batik work from IKM Batik Semarang 16 of the five motifs have bright, dominant colors. line elements, decorations do not experience too much composition, either distortion or stylization. The cultural ecology aspect of batik by IKM Batik Semarang 16 refers to certain themes and categories and represents Semarang from a natural, physical and socio-cultural perspective.